Integrating Lean Implementation and Relayout Design for Efficiency Improvement - Muhammad Ikhlasul Amal; Nina Aini Mahbubah (Department of Industrial Engineering Universitas Muhammadiyah Surakarta, 2022)
Eliminating non-value-added (NVA) activities is a comprehensive solution to achieve efficiency in manufacturing industry production processes. Inefficiency arises whether the production facility and equipment are recent or timeworn. Division. Soybean Production PT. YZ seeks to evaluate the inefficiencies in the relatively new soybean production and packaging plan. The incompatibility of the layout of the production floor facilities was identified as the leading cause of the inability of the Soybean Production Division to meet consumer demands. This study aims to make the production floor layout based on material handling costs, provide good layout alternatives, minimize lead times, and increase cycle efficiency in production processes. The research method integrates Systematic Layout Planning (SLP) and the Lean Manufacturing approach. Value Stream Map (VSM) as a study result distinguishing waste, namely motion and waiting for the material transfer process, which leads to non-value added activity. The best alternative layout proposal was obtained, namely the second Alternative, with the results of minimizing material handling costs by 26% and time-wasting by 19%. VSM and Relayout design provide significant improvement in eliminating losses as well as efficiency improvement.